1990
DOI: 10.1002/1097-0142(19900401)65:7<1552::aid-cncr2820650717>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of squamous cell carcinoma antigen as a new marker for lung cancer

Abstract: Carcinoembryonic antigen (CEA) is the only tumor marker of proven, although limited, value for the management of patients with non-small cell lung cancer (NSCLC). The authors have prospectively assessed the potential value of a new tumor marker, squamous cell carcinoma antigen (SCC Ag), in a large series of patients with advanced lung cancer (LC). Squamous cell carcinoma antigen and CEA levels were measured in 382 healthy persons (N1 group), 90 patients with benign pulmonary diseases, and 291 patients with LC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 9 publications
1
15
0
3
Order By: Relevance
“…Our results were in agreement with Szymańska-Chabowska et al's and Cho et al's study that higher serum (squamous cell carcinoma antigen) SCC Ag levels and a distinct synergistic reaction with the number of smoked cigarettes (Szymańska-Chabowska et al, 2004;Cho et al, 2013). Smoking habits did not influence the serum concentrations of SCC Ag in lung cancer (Body et al, 1990). TNF-a levels resembled more the smoking habits (P<0.001, OR=5.98, 95% CI: 2.57-13.87) and alcohol consumption (P=0.012, OR=2.67, 95% CI: 1.24-5.72) of the coke oven workers.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in agreement with Szymańska-Chabowska et al's and Cho et al's study that higher serum (squamous cell carcinoma antigen) SCC Ag levels and a distinct synergistic reaction with the number of smoked cigarettes (Szymańska-Chabowska et al, 2004;Cho et al, 2013). Smoking habits did not influence the serum concentrations of SCC Ag in lung cancer (Body et al, 1990). TNF-a levels resembled more the smoking habits (P<0.001, OR=5.98, 95% CI: 2.57-13.87) and alcohol consumption (P=0.012, OR=2.67, 95% CI: 1.24-5.72) of the coke oven workers.…”
Section: Discussionsupporting
confidence: 92%
“…However, current serum biomarkers for NSCLC such as carcino embryonic antigens (CEA) and squamous cell carcinoma antigen do not have sufficient sensitivity and specificity required for early detection of NSCLC. 4,5 It is now clear that malignant transformation occurs by changes in cellular gene expression with subsequent clonal proliferation. Altered gene expression in malignant cells may lead to the expression of aberrantly expressed proteins recognized by host immune system.…”
Section: Uiccmentioning
confidence: 99%
“…O'CONNOR and DEFTOS [96] observed chromogranin A in a wide variety of neuroendocrine tumours. NAKAJAMA et al [94] found a positive reaction to 189 a recent study on 291 patients (129 with SCLC and 162 with NSCLC, including 36 with SCC), BODY et al [60] measured both CEA and SCC-ag, and reached the following conclusions: 1) the use of SCC-ag is inappropriate for lung cancer screening in asymptomatic patients; 2) high values can be observed in patients with benign pulmonary disease; 3) SCC-ag serum levels, in contrast to CEA, are not determined by smoking habits; 4) SCC-ag has lower sensitivity but higher specificity than CEA in SCC; and 5) high pretreatment levels are indicative of a negative prognosis. Another study by MIZUSHIMA et al [46] confirmed these results.…”
Section: Chromogranin Amentioning
confidence: 99%